A New Method to Calibrate Robot Visual Measurement System. (25th November 2013) - Wang, Yali; Wei, Zhenzhong; Shao, Mingwei; Zhang, Guangjun
Abstract : This paper presents a new method to calibrate the robot visual measurement system. In the paper, a laser tracker is used to calibrate the robot twist angles. Each axis of the robot is moved to many positions and the positions measured by the laser tracker fit a plane. The normal vectors of the planes are the directions of the Z axes. According to the definition of the robot kinematics model parameters, the errors of the twist angles can be calculated. The joint angles zero offsets are calibrated by the constraint that the rotation relationship between the world frame and the robot base frame is relatively constant. A planar target with several parallel lines is used to obtain the pose of the camera relative to the planar target by the lines in the target plane and the vanishing line of the plane. The quantum behaved particle swarm optimization (QPSO) algorithm is used to calculate the parameters. Experiments are performed and the results show that the accuracy of the robot visual measurement system is improved about 10 times after being calibrated.